Effectiveness of Electronic Court System (E-Court) in Kuningan Religious Court Based on PERMA Number 7 of 2022 - Anthon Fathanudien; Asep Ridwan Firdaus (INKLUSIF (JURNAL PENGKAJIAN PENELITIAN SYARIAH DAN ILMU HUKUM), 2025)
The Kuningan Religious Court, as part of the national justice system, also implements E-Court based on applicable regulations, including PERMA Number 7 of 2022. This study aims to evaluate the impact of E-Court implementation on case resolution time and litigation costs at the Kuningan Religious Court. The research method used by the author is empirical juridical, where this research is descriptive and tends to use analysis and theory as a guideline so that the study focuses on facts in the field. The findings are to develop more measurable and specific effectiveness indicators that are relevant to the context of the Kuningan Religious Court and PERMA Number 7 of 2022. For example, not only measuring the general case resolution time but also measuring the impact of E-Court on specific stages regulated in the new PERMA. With the implementation of PERMA Number 7 of 2022, the Kuningan Religious Court has contributed to the realization of the principles of fast, simple, and low-cost justice. The conclusion obtained is that E-Court at the Kuningan Religious Court is systematically starting from online registration (E-Filling), online payment (E-Payment), online summons of parties (E-Summon), and electronic trials (E-Litigation) has been effective. There are several supporting and inhibiting factors in the Implementation of E-Court, namely in terms of supporting factors are Human Resources (HR) and Adequate Facilities and Facilities, Reducing Litigation Costs and Good Internet Networks while inhibiting factors Constrained Calls and e-court System Network Error.